2020
DOI: 10.5222/head.2020.10692
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vibration on Pain and Anxiety During Intravenous Blood Sampling in Adults

Abstract: Aim: This quasi-experimental, descriptive study analyzed the effect of vibration on pain and anxiety during venipuncture in adults. Methods: Data was collected in the Phlebotomy Unit in a University Hospital. The sample consisted of 401 patients randomly selected (control group, n=197; intervention group, n=204) between 18 and 82 years old. The intervention group experienced vibration during venipuncture whereas the control group had the standard phlebotomy procedure. Pain was measured using the Visual Analogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
1
Order By: Relevance
“…Our study showed that adult patients who are waiting for venepuncture procedure in phlebotomy unit had a lower anxiety score compared to other studies that measure the anxiety score for venepuncture using the same STAI Questionnaire [15]. On the other hand, our finding also is not far from the study findings from Turkey [16] on the effect of vibration on pain and anxiety during venipuncture. The control group who only had a J Ment Health Soc Behav…”
Section: Discussioncontrasting
confidence: 67%
“…Our study showed that adult patients who are waiting for venepuncture procedure in phlebotomy unit had a lower anxiety score compared to other studies that measure the anxiety score for venepuncture using the same STAI Questionnaire [15]. On the other hand, our finding also is not far from the study findings from Turkey [16] on the effect of vibration on pain and anxiety during venipuncture. The control group who only had a J Ment Health Soc Behav…”
Section: Discussioncontrasting
confidence: 67%